Motorization Innovations in Increasing Fishermen's Income in Liukang Kalmas District, Pangkep Regency - Junaid; Ansyari Mone; Muchlas M Tahir (Journal La Bisecoman, 2020)
This study aims to determine motorization innovation in increasing the income of fishermen in the Liukang Kalmas Subdistrict of Pangkep Regency and to determine the supporting factors and inhibiting factors of the innovation. This type of research is qualitative descriptive, data collection is done using interviews by selecting informants through probability sampling. Data is collected from observations, interviews, and documentation. The results of this study indicate that boats with motor engines are important to be used by fishermen who are specifically used to search for Torani or flying fish that have high economic value, through motorization innovations fishermen's income is much more increased not only limited to the needs of fishermen families but can provide additional on income. Then the supporting factor is government assistance in the form of facilities for fishermen who are poor and less able in the form of engines or motorboats. While the inhibiting factors are natural conditions that do not support and the cost of repair and operation of the ship resulting in fishermen's income cut.